Evaluation of rhBMP‐2 and bone marrow derived stromal cell mediated bone regeneration using transgenic fluorescent protein reporter mice. Issue 12 (3rd March 2014) - Gohil, Shalini V.; Adams, Douglas J.; Maye, Peter; Rowe, David W.; Nair, Lakshmi S.
Abstract The aim of the study is use of transgenic fluorescent protein reporter mouse models to understand the cellular processes in recombinant human bone morphogenetic protein‐2 (rhBMP‐2) mediated bone formation. Bilateral parietal calvarial bone defects in Col3.6Topaz transgenic fluorescent osteoblast reporter mouse were used to understand the bone formation in the presence and absence of rhBMP2 and/or Col3.6Cyan bone marrow derived stromal cells (BMSCs), using collagen‐hydroxyapatite matrix (Healos) as a biomaterial. The bone regeneration was not confined to the site of BMP‐2 implantation and significant bone formation was observed in the neighboring defect site. Osteogenic cellular activity with overlying alizarin complexone staining was observed in both the defects indicating host cell induced mineralization. However, implantation of BMSCs along with rhBMP‐2 demonstrated a donor cell derived bone formation. The presence of rhBMP‐2 did not support host cell recruitment in the presence of donor cells. This study demonstrates the potential of multiple fluorescent reporters to understand the cellular processes involved in the bone regeneration process using biomaterials, growth factors, and/or stem cells. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4568–4580, 2014.